Germination behaviour and field performance of garden pea (Pisum sativum) in relation to seed ageing - PANDITA, V K; NAGARAJAN, SHANTHA (The Indian Journal of Agricultural Sciences, 2014)
An experiment was carried out during the winter (rabi) season 2000-2001 with garden pea (PiSWl1 sativum L.s.l.) varieties’ Arkel’ and ’Bonneville’, to assess the effect of ageing on seed quality and productivity. Laboratory germination, speed of germination and vigour were significantly reduced from 97.5 to 87.0%, 21.8 to 15.8 and 1 650 to 1 164, respectively, as the ageing process progressed from 8 to 32 months. Conductivity of seed leachates increased with ageing process (16.7 to 24.3 m Siemens/seed). The field experiment showed no significant reduction in yield and yield-attributing characters up to 32 months of ageing in’ Arkel’ (1.82 to 1.67 tonnes/ha), while in ’Bonneville’ reduction started after 20 months (1.97 to 1.68 tonnes/ha).